Uncovering the Integration of Technology and Global Curriculum in Shaping Future Accountant Professionals: Case Studies at the University of Muhammadiyah Bandung and University of Kuala Lumpur - Tania Ningrum; Erfan Erfiansyah; Nur Aisya Putri Binti Suratman (Greenation International Journal of Economics and Accounting, 2025)
Uncovering the Integration of Technology and Global Curriculum in Shaping Future Accountant Professionals: A Case Study at the University of Muhammadiyah Bandung and the University of Kuala Lumpur. This study aims to analyze students' perceptions related to the integration of technology and global curriculum in accounting education at the University of Muhammadiyah Bandung (UMBandung) and Universiti Kuala Lumpur (UniKL). The method used is an exploratory case study with a qualitative approach. Data were collected through in-depth interviews with students from both institutions and analyzed inductively. The results show that although the curriculum has adopted international standards such as IFRS and ISA, the application of global materials such as international audits and cross-border taxation is still limited. UniKL students are more familiar with modern accounting software and certification programs, while UMBandung students excel in a value-based ethical approach. Cross-cultural communication and teamwork training is considered effective, but multinational work simulations still need to be improved. This study recommends strengthening technology-based curriculum, increasing university cooperation with industry, and periodic curriculum evaluation to align with global market demands and future developments of the accounting profession.